Webinar - CCAFS Annual Reporting 2018 - Abreu, David; Loboguerrero Rodriguez, Ana María; Tobon, Hector; Schuetz, Tonya (2019)
A webinar covering CCAFS Data Management Strategy including planning and reporting processes.